(untitled) (Research, Society and Development, 2022)
Ethnomathematics has been studied on some research in the field of Mathematics Education and several authors emphasize that Ethnomathematics approach in the classroom can bring important contributions to the teaching and learning of Mathematics. In this context, it is relevant to analyze the way in which academic works use ethnomathematics knowledge in the classroom. Thus, the present research was carried out with the objective of analyzing academic works that show proposals that use Ethnomathematics in the teaching of Mathematics and its implementations, which were published in Annals of five editions of the Encontro Nacional de Educação Matemática (National Meeting of Mathematics Education), in the period from 2007 to 2019. Thus, 20 papers were selected and analyzed. Those academic works were related to ethnomathematics referring to different ethnic/social contexts, with emphasis on the “farming”. The proposed activities were developed at various levels and teaching modalities, among which Youth and Adult Education stand out. The mathematical contents taught in the proposals presented in these academic works are varied, however, there is a predominance of Geometry concepts. Furthermore, we identified a link between the Ethnomathematics approach and the methodologies of Mathematical Investigation, Problem Solving and, especially, Mathematical Modelling approach. Finally, the analyzes indicate that the contributions of the activities with a developed Ethnomathematics approach were related to “Knowledge and appreciation of knowledge elaborated by various ethnic/social groups” including the students themselves; “Students’ Mathematical Learning” and “Recognition of the relationships between knowledge learned and shared at school and outside it”.